Two new genera of coastal Talitridae (Amphipoda: Senticaudata) from Chile, with the first record of Platorchestia Bousfield, 1982 in the southeastern Pacific coast - Pérez-Schultheiss, Jorge; Fernández, Leonardo D.; Ribeiro, Felipe Bezerra (Zootaxa, 2024)
Using samples of talitrid amphipods collected on the coast of Chile, we describe two new monotypic genera characterized by particular types of sexual dimorphism, and we report the first record of the genus Platorchestia Bousfield, 1982 in the southeastern Pacific coast. In the subfamily Platorchestiinae, the genus Atacamorchestia gen. nov. and its new species Atacamorchestia atacamensis sp. nov. was collected in marine rocky coasts, in several localities in northern Chile. This new taxon is characterized principally by presence of T setae in male appendages, a feature shared with the genus Vallorchestia from Australia, but with a different distribution of these structures. The first specimens of Platorchestia in the Southeastern Pacific were obtained in Antofagasta, northern Chile, however they were identified only to genus level because a more in-depth taxonomic analysis will be necessary to determine their status. Finally, in the subfamily Talitrinae, Lafkenorchestia gen. nov. and its new species Lafkenorchestia oyarzuni sp. nov. were found on rocky marine shores and in estuaries in southern Chile, between La Araucania and Los Lagos regions. This new taxon is characterized by distinct modifications in basis and merus of male pereopod 7, showing some morphological similarities with the New Zealand genera Subantarctorchestia and Pictonorchestia. For each species, descriptions and illustrations are presented.